PERANCANGAN MESIN POLES SERBA GUNA (MODIFIKASI CAMSHAFT/NOKEN AS) - Gunawan, Yuspian; Delly, Jenny; Sawaludin, La; Murila, Samsul; Solihin, Dedy (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
Design of All-purpose polishing machines (modification camshaft) polishing camshaft with the purpose of increase or widen the camshaft and increase the volumetric efficiency and changed the character of a machine, in order for the machine to produces greater power and according to the needs. Design of All-purpose polishing machines (modification camshaft) designed to work with a round with the requirements at the time of work. In addition this engine designed no longer using human power as its main driving force but by an electric motor. The results of design generates a work product image design all-purpose polishing machines (modification camshaft) includes pictures, mounting an electric motor, picture holder dibble camshaft, and picture transmission system. Powerplant engine is electric motor 1 HP (± 25 watts). A modified camshaft engine has generated a strong construction and engine specifications dimensional length 350 mm x 250 mm width x height 230 mm with stand construction is made of profile L i.e. 250 x 170 x 90 mm.Keywords: Design, of all-purpose polishing machines (modification camshaft).